2013
DOI: 10.2298/pif1304265g
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of chlorpyrifos to white mustard (Sinapis alba L.) and maize (Zea mays L.): Potential indicators of insecticide presence in water

Abstract: SuMMARYChlorpyrifos is a hazardous insecticide and important pollutant of the environment. The EU Directive 2008/105/EC lists it as one of the priority water pollutants. Its presence is mainly detected by chemical methods but, since biological tests have gained in importance in the last few years, this study aimed to assess the potentials of white mustard (Sinapis alba L.) and maize (Zea mays L.) as indicators of water pollution. The phytotoxic effects of chlorpyrifos (rates 0.05-10µg a.i./l) were assessed bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The test species, white mustard (Sinapis alba L.) expressed different sensitivity levels to contamination. This is consistent with the findings of Gvozdenac et al [2013] where tolerance levels of crops are species dependent and vary under different stress intensities (concentrations and types of pollutants) and growth stages (germination, emergence, vegetative growth, etc.). In the present study, two types of sewage sludge: dewatered and anaerobically stabilized sludge with dry matter content of about 24%, and dewatered sludge "Palikal" with dry matter content of about 92% caused phytotoxic effects on the tested plant species, manifesting as root and shoot growth reduction or total inhibition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The test species, white mustard (Sinapis alba L.) expressed different sensitivity levels to contamination. This is consistent with the findings of Gvozdenac et al [2013] where tolerance levels of crops are species dependent and vary under different stress intensities (concentrations and types of pollutants) and growth stages (germination, emergence, vegetative growth, etc.). In the present study, two types of sewage sludge: dewatered and anaerobically stabilized sludge with dry matter content of about 24%, and dewatered sludge "Palikal" with dry matter content of about 92% caused phytotoxic effects on the tested plant species, manifesting as root and shoot growth reduction or total inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…Biological assays have been used for several decades in risk assessment and detection of water/sludge contamination have mainly involved aquatic invertebrates (chironomid larvae, mosquitoes, dragon flies, prawns, shells and hydras), aquatic vertebrates such as fish and algae, and aquatic plants such as Lemna minor L. Based on these facts, it is obvious that the use of plants as indicators of contamination has been generally underestimated and rarely used in toxicological studies, compared to animal organisms [Moor and Kroege, 2010]. However, the significance of research that involves phytoindicators should not be neglected because such data show the bioavailability of contaminants and enable risk assessment and creation of protocols for remediation of contaminated sites [Gvozdenac et al, 2013].…”
Section: Resultsmentioning
confidence: 99%
“…Chlorpyrifos was found to have inhibitory effect on germination in Pinus halepensis seeds and seedlings (Olofinboba and Kozlowski 1982), annual grass and annual forb (Gange et al 1992), ryegrass (Lolium multiflorum) (Korade and Fulekar 2009), different vegetables (Zhang et al 2013), Cenchrus setigerus and Pennisetum pedicellatum (Dubey and Fulekar 2011), white mustard (Sinapis alba L.), maize (Zea mays L.) (Gvozdenac et al 2013), and soybean (Glycine max) (Bassey et al 2015). The intensity of toxicity on seed germination energy, seed germination, survival, and subsequent growth increases with chlorpyrifos concentration (Dubey and Fulekar 2011;Gvozdenac et al 2013). It has also been reported to exert detrimental effect on the root biomass, root appearance and disappearance, and root density (Dawson et al 2003;Singh et al 2003a).…”
Section: Toxicity On Plantsmentioning
confidence: 99%
“…A standard filter paper method [20] was used for the test. White mustard seeds (30 per replication, with three replications) were placed in Petri dishes (Ø15 cm) on filter paper moistened with 20 ml of solution [9]. For water toxicology 3 ml of original water was used for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Wierzbicka and Obidzinska [8] demonstrated that seed coats were the main barrier to contaminants, and prevent contamination of embryos until the seed coat is torn apart by the germinating embryonic root. Germination of seeds may depend on such parameters as the seed structure and seed coats [9]. Plant species are recommended by the U.S. Environmental Protection Agency (EPA) and the Organization for Economic Cooperation and Development (OECD).…”
mentioning
confidence: 99%